Scientific studies of mobile applications that address the concepts of Physical discipline in Libras (Research, Society and Development, 2020)
Digital technologies are increasingly present in people's daily lives, of the most varied age group and social class. Modern society is also marked by the social inclusion of people with disabilities. The inclusion of disabled people begins in the classroom, with the school assuming the role of integrator. For deaf students, this integration must occur through a Libras interpreter, which is one of the communication channels between the deaf student and his colleagues, teachers and school staff. However, this interaction is sometimes limited by the fact that deaf students do not have a 24-hour interpreter at their disposal. The use of a mobile device can be a useful tool in the inclusion of the deaf, since they can use their devices to access applications that allow the combination of the Portuguese language with Libras. Therefore, the objective of this work was to conduct a search in order to identify whether this technology is already available and able to be explored by deaf students in the teaching of Physics. The analysis was limited to the period from 2014 to 2019, as it is a time of strong technological expansion. A search of the GooglePlay Store resulted in 94 applications involving the word Libras, 57 of which were of Brazilian origin and 37 were foreign. Of this total, only one Brazilian application involved teaching Physics. Thus, the research showed that the possibilities of applications that favor the teaching and learning processes of Physics to deaf students are still scarce.